Study of biological parameters during composting of sewage sludge - Kabbashi, Nassereldeen Ahmed; Fakhru’l-Razi, Ahmadun; Azni, Idris (Institute Technology Brunei, 2003)
The development of appropriate strategies for the treatment and disposal of sewage sludge is a major problem for all countries throughout the World. Sludge treatment and disposal not only represents about half of the total costs of municipal wastewater collection, but it is also strongly regulated, more so than almost and other forms of waste. The sewage sludge used in this study was collected from Taman Sri Nanding and Taman Koperasi Indah Water Konsortium treatment plants Malaysia. The sludges had a higher moisture content around 80% to 82% and a low C/N ratio of 7 to 8.5. Both sludges had more or less similar characteristics. However pH of sludge from Taman Sri Nanding was lower than that of Taman Koperasi. Sawdust had a low moisture content of 10-20% and a high C/N ratio ranging from 166.6 to 285. Hence sawdust was homogenized with the sludge to increase the C/N ratio of the sludge, which inoculated with a mixture of P.chrysosporium and Trichoderima harzinum. This also reduced the moisture content to the optimal level for composting. In a medium scale horizontal drum bioreactor occurred for 21 days and one month curing, the biological parameters were monitored to evaluate the effect of sawdust on the composting process.